Unveiling hepatitis E virus diversity in Sudan's internally displaced populations: a molecular epidemiology approach - Osman, H.A.; Bakr, W.M.K.; Hashish, M.H.; Elkhidir, I.M.; Bedri, S.; Oyola, Samuel O.; Norder, H.; El-Wahab, E.W.A. (BioMed Central, 2025)
Background: Hepatitis E virus (HEV) is recognized as a cause of acute viral hepatitis, particularly in low-resource and humanitarian settings, although its burden varies across different populations and geographic areas. Internally displaced persons (IDPs) are at high risk due to inadequate sanitation and contaminated water. This study aimed to characterize the molecular epidemiology and genotypes of HEV among IDPs in Al-Azaza Camp, Blue Nile State, Sudan.